Integrated smart farm system for Centella asiatica L. cultivation: development and assessment of multi-tier cultivation effects on bioactive compound production - Lee, Hyeonbyeong; Baek, Jeonghyun; Im, Donghyuk; Heo, Jeongwook; Kim, Taehyun (Frontiers in Plant Science, 2025)
IntroductionTraditional soil-based cultivation of Centella asiatica L. faces seasonal limitations and quality inconsistency.MethodsThis study developed and assessed a smart farm system incorporating Deep Flow Technique (DFT) hydroponics for stable, year-round production with consistent bioactive compound profiles. System development was conducted at the National Institute of Agricultural Sciences, followed by a six-month field assessment at Chungju Agricultural Technology Center, South Korea. The cultivation system comprised a 99 m² greenhouse with a 19.2 m² active hydroponic area, maintaining key environmental parameters.ResultsWe observed differential bioactive compound accumulation between cultivation tiers. Madecassic acid content was 2.3-fold higher in the LED-equipped tier (1.25 ± 0.04 mg/g) versus the fluorescent-equipped tier (0.54 ± 0.03 mg/g, p<0.001).DiscussionThe system demonstrated operational reliability, enabling year-round production and establishing a technological foundation for controlled environment medicinal plant cultivation with standardized compound profiles.